The Teachers Perception Of Developing Teaching Materials Of Local History By Critical Pedagogy Approach In SMAN 3 Ponorogo - Nunuk Suryani, Nia Ulfia Krismawati, Warto (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The globalization creates a competitive situation among the young generations around the world. Thedanger of globalization continued to threaten the sense of nationalism and nationality will have an impacton the country which has a multicultural character. Differences in ethnicity can be a time bomb ready toexplode if not addressed wisely. The education has an important role in providing solutions related to theproblems the caused by globalization. In this case, the history of education has a role in building nationalawareness and respect for diversity. The local history of each regions containing inspirational educationvalues can be a means of forming the character of the young generations. It is necessary for innovationthat one of this is the development of teaching materials that suit of the learners needs. This researchdescribed how far teachers are aware of the importance of local history as the subject of history materials,the material development Efforts of local history as a learning source, and how the teachers response oncritical pedagogy approaches a paradigm in the development of teaching materials of local history. Themethod used in this research is the qualitative method. Data collected by using observation, interview,and inquiry. The research conducted at SMAN Ponorogo by focusing excavation of existing local history.This study tries to demonstrate several things, (1) the urgency of the development teaching materials oflocal history, (2) the teachers perception of the importance of developing teaching materials of localhistory, (3) the perception of teachers about the critical pedagogy approaches the basic for developingteaching materials of local history.Keywords:Teaching Materials; Local History; Critical Pedagogy Approach.